PENGARUH KOMPETENSI KEPRIBADIAN GURU TERHADAP MOTIVASI BELAJAR DAN IMPLIKASINYA TERHADAP PRESTASI BELAJAR - Mudianah, Sulam; Handayani, Femi; Aisyah, Iis (Journal of Business Education and Social, 2022)
This study aims to determine the effect of teacher personality competence on learning motivation and the effect of learning motivation on learning achievement in Public and Private Senior High Schools in Tangerang City. The samples in this research were students of SMA Negeri 6 Kota Tangerang and SMA Syekh Yusuf Kota Tangerang. Data collection in this study used a questionnaire containing 20 statements which were distributed to 100 respondents. This research is a correlational research and a quantitative descriptive approach. Methods of data collection using questionnaires and documentation. Cronbach's Alpha Test. Analysis prerequisite test consists of normality test, linearity test, multicollinearity test, heteroscedasticity test. hypothesis testing consists of multiple linear regression tests. The results showed that partially, personality competence influences learning motivation and learning motivation influences learning achievement.